Requirements and tasks of educators in the function of moral development and education of young children in preschool programs/curricula in the Republics of Serbia and the Republic of Croatia - Apostolović, Ivana (Norma, 2022)
The paper analyzes and compares the content of current preschool programs/curricula in the Republic of Serbia and the Republic of Croatia through a detailed presentation of the requirements and tasks of preschool teachers in the function of moral development and education of young children. The aim of our research is to determine whether and to what extent the programs/curricula of preschool education in the Republic of Serbia and the Republic of Croatia differ in terms of specifying the requirements and tasks of the teachers in relation to moral development and education of children. The descriptive and comparative methods and the procedure of analysis of the content of program documents are applied in the paper. The results of our research indicate that in the Republic of Serbia and the Republic of Croatia in preschool programs / curricula, the requirements and tasks of teachers are presented in the function of moral development and education of children, but in different ways. The analyzed programs/curricula recognize the same tasks related to moral development, and differ from each other when it comes to their concretization, and there are some differences in their formulation. Starting from concrete tasks, teachers, the creators of their own practice, have the opportunity to better understand the needs of children through them, but also to choose from clearly separated tasks what is most needed to encourage and develop children in a certain period of time, within moral development.
Keywords: child; moral education; preschool teacher; preschool program/curriculum